Election During Covid-19 Pandemic: Constitutional Perspectives - Mohd Anuar, Haslinda (Global Academic Excellence, 2020)
The spread of Covid-19 requires a new norm in all aspects of life. To a democratic country, the conduct of an election is a must to ensure the system is in line with the rule of law. Malaysia announced her ‘lockdown’ on 18th March 2020 after the increase of the numbers of Covid-19 positive cases. Since then, three elections have been conducted. This paper aims to explore the constitutional provisions relating to elections and study the methods elections been conducted during the pandemic. To curb the spread of the Covid-19 virus, suggestions are made to tighten the Standard Operating Procedures (SOPs) and the last straw of proclaiming emergency. In conclusion, the constitutional provisions must be strictly complied with and cooperation from all walks of life is important to combat the pandemic